2020
DOI: 10.1101/2020.08.13.20167452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abusers indoors and coronavirus outside: an examination of public discourse about COVID-19 and family violence on Twitter using machine learning

Abstract: Purpose: This brief report aims to provide the first large-scale analysis of public discourse regarding family violence and the COVID-19 pandemic on Twitter. Method: We analyzed 301,606 Tweets related to family violence and COVID-19 from April 12 to July 16, 2020, for this study. We used the machine learning approach, Latent Dirichlet Allocation, and identified salient themes, topics, and representative Twitter examples. Results: We extracted nine themes on family violence and COVID-19 pandemic, including (1) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A limited number of studies to date have specifically examined discussion of domestic violence during the COVID-19 pandemic using data gleaned from Twitter. 47 One study focused on assessing children's exposure to violence during the COVID-19 pandemic. 49 Research by Al-Rawi et al 48 highlighted gender differences in how individuals used Twitter during COVID-19 to discuss risk of violence as well as other harms.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies to date have specifically examined discussion of domestic violence during the COVID-19 pandemic using data gleaned from Twitter. 47 One study focused on assessing children's exposure to violence during the COVID-19 pandemic. 49 Research by Al-Rawi et al 48 highlighted gender differences in how individuals used Twitter during COVID-19 to discuss risk of violence as well as other harms.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
“…Examining the Twitter commentary relating to IPV during the COVID-19 is a useful strategy for gaining a conceptual understanding of the context of IPV during this time in history. Notably, prior analyses by Xue et al 46 , 47 emphasize Twitter users’ concerns regarding the ways in which the global COVID-19 pandemic increased risk for family violence (including IPV, child abuse, and elder abuse), as well as rates of homicide, suicide, and mental health concerns. Additionally, Al-Rawi et al 48 found significant differences in public discourse around COVID-19 on Twitter based on gender.…”
mentioning
confidence: 99%
“…Indeed, increased rates of poverty (Van Lancker & Parolin, 2020) and child abuse (Baron et al, 2020;Griffith, 2020) have already been reported during the pandemic. Domestic abuse and family violence have also been reported as increasing dramatically during the COVID-19 pandemic (Bradbury -Jones & Isham, 2020;Campbell, 2020;Humphreys et al, 2020;Mazza et al, 2020;Piquero et al 2020;Usher et al, 2020;Xue et al, 2020). All of these issues are likely to add additional burden to already wrought health systems, but also have the potential to impact on social and educational engagement, health, and overall wellbeing (Rothstein & Olympia, 2020).…”
Section: Covid-19 and Its Impacts On Educationmentioning
confidence: 99%
“…The novel coronavirus (COVID-19) pandemic has raised widespread concern about children's exposure to family violence ( Cappa & Jijon, 2021 ). Following initial lockdowns to address COVID-19, significant increases in domestic violence calls were observed ( Leslie & Wilson, 2020 ; Nix & Richards, 2021 ; Xue et al, 2020 ). Although there was a decrease in child abuse calls ( Department of Health and Human Services, 2018 ; Jonson-Reid et al, 2020 ), this may be due to a lack of visibility rather than an absence of maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, the COVID-19 pandemic is likely to increase family violence through its impact on situational variables associated with family violence and these increases are more likely to occur in families already at risk for violence (i.e., families with a prior history of violence, caregivers who experience increased emotion reactivity). Currently, there is a lack of research on predictors of family violence in the COVID-19 pandemic ( Xue et al, 2020 ). Past public health crises that similarly impacted daily functioning have been linked to spikes in spousal and child abuse that decrease over time ( Davidson & McFarlane, 2006 ; Santos, 2020 ).…”
Section: Introductionmentioning
confidence: 99%